The Use of the TARGET Antibiotic Checklist to Support Antimicrobial Stewardship in England's Community Pharmacies - Sejal Parekh; Catherine V. Hayes; Jill Loader; Diane Ashiru-Oredope; Kieran Hand; Gemma Hicks; Donna Lecky (MDPI AG, 2023)
Antimicrobial Stewardship (AMS) requires effective teamwork between healthcare professionals, with patients receiving consistent messages from all healthcare professionals on the appropriate antimicrobial use. Patient education may reduce patients' expectations to receive antibiotics for self-limiting conditions and reduce the pressure on primary care clinicians to prescribe antibiotics. The TARGET Antibiotic Checklist is part of the national AMS resources for primary care and aims to support interaction between community pharmacy teams and patients prescribed antibiotics. The Checklist, completed by the pharmacy staff with patients, invites patients to report on their infection, risk factors, allergies, and knowledge of antibiotics. The TARGET antibiotic checklist was part of the AMS criteria of England's Pharmacy Quality Scheme for patients presenting with an antibiotic prescription from September 2021 to May 2022. A total of 9950 community pharmacies claimed for the AMS criteria and 8374 of these collectively submitted data from 213,105 TARGET Antibiotic Checklists. In total, 69,861 patient information leaflets were provided to patients to aid in the knowledge about their condition and treatment. 62,544 (30%) checklists were completed for patients with an RTI; 43,093 (21%) for UTI; and 30,764 (15%) for tooth/dental infections. An additional 16,625 (8%) influenza vaccinations were delivered by community pharmacies prompted by discussions whilst using the antibiotic checklist. Community pharmacy teams promoted AMS using the TARGET Antibiotic Checklist, providing indication-specific education and positively impacting the uptake of influenza vaccinations.